Strengthening Indonesia’s Role In Indian Ocean Through IORA - Ari Setiyanto (Jurnal Pertahanan: Media Informasi ttg Kajian & Strategi Pertahanan yang Mengedepankan Identity, Nasionalism & Integrity, 2017)
Indonesian government concerned to determine the future of the Pacific and Indian Ocean Region through new vision as the world maritime fulcrum. Significant growth in Indian Ocean region urges a cooperation approach between littoral countries located around the Indian Ocean and lead the establishment of Indian Ocean Rim Association (IORA). The cooperation will lead to the accomplishment of the Indonesia’s national interests. On the other side, the potential trade volume in the Indian Ocean region cannot be reached because of limited maritime infrastructure that facilitates the current trade. IORA should develop a master plan or blueprint on connectivity that will provide the infrastructure development agenda with the Public-Private Partnership to accelerate the infrastructure development. By this situation, the development of maritime infrastructure can be a double advantage for Indonesia because it will connect APEC and IORA. The important things to consider in terms of security is a potential threat both to security and defense if the government decided to open and build a deep seaport in Western Sumatera and Java Island.It is important to evaluate the potential threats and challenges if Indonesia wants to be a fulcrum of world maritime activity.